An In vitro Comparative Study to Evaluate The Apical Seal of Root Canals Prepared by Rotary Versus Reciprocating Wave-One Nickel Titanium System - Rasha M. Al-Shamaa; Makdad N. Chakmakchi; Karam A. Thiab (University of Mosul, College of Dentistry, 2014)
Aims: The aim of present study is to assess the apical seal of root canals prepare by two different preparation techniques (Rotary and reciprocating technique) . Materials and Methods: Forty extracted human, single-rooted lower premolar teeth were decoronated at the cement-enamel junction (CEJ). The working length was determined for each tooth. The samples were divided into 2 experimental groups, each one consisted of 20 prepared teeth: group 1, rotary conventional preparation by using Wave-One file. group2, reciprocate instrumentation with Wave-One file. After instrumentation was completed then the teeth obturated with Single-cone technique related to this systems. Zinc oxide euginol (ZOE) sealer was used as a root canal sealer in this study. A dye penetration method was used to evaluate the apical seal and the teeth were cleared then apical leakage was measured using a stereomicroscope at (x10 magnification). The statistical analysis performed by Independent t-test. Results: Wave-One file instrumented by Reciprocation instrumentation technique was significantly differ from Rotary instrumentation technique for root canal preparation . The Reciprocation group registered better apical seal than Rotary group. Conclusions: Apical seal with the Wave-One Reciprocation technique and conventional Wave-One rotary approach were significantly difference. The Wave-One Reciprocation technique was markedly registered better apical seal than Wave-One rotary technique.